Digitisation of films and selection of films for digitisation from the perspective of users (Libellarium: journal for research in the field of information and related sciences, 2023)
Purpose. The selection of films that archivists carry out today has an important impact on the future configuration of digitalised and virtually accessible film collections. Given the responsibility that this task entails, we consider it interesting to explore what the different profiles of the users of film archives think about selection and digitisation of films.Approach/Methodology/Design. To this end, structured interviews were conducted with 31 subjects belonging to four groups of users: film researchers, film professionals, journalists/ film critics, and last year audio-visual communication undergraduates from the Universityof Seville.Findings. The most notable results, which do not differ in essence from what is known in the archival field, include, on the one hand, the unanimous view that digitisation is an effective way of conserving audio-visual memory and fostering public interest in film collections and archives and, on the other, that when films have to be selected for their digitisation, this should be done following rigorous and systematic selection criteria, thus avoiding the detrimental effects of random methods. Lastly, some future research lines are offered.Originality/Value. All the bibliography consulted view topics relating to film selection and digitisation exclusively through the prism of archival and library and information sciences. Namely, these studies are restricted to these specific areas of knowledge and aimed at professional and experts in the field. For that reason, it may be interesting to explore other viewpoints and perspectives that go beyond purely technical, theoretical or methodological approach to film curation.
Keywords: archival selection of films; film archives; film archiving; film digitisation; film librarianship